1970
DOI: 10.1021/ed047p519
|View full text |Cite
|
Sign up to set email alerts
|

A new, long-lasting luminol chemiluminescent cold light

Abstract: Chemiluminescent Cold LightOnly a few organic and inorganic compounds are known to emit appreciable amounts of visible cold light. Very few chemicals are reasonably efficient in producing cold light for prolonged periods of time (longer than one hour) and at present there are about five chemiluminescent reactions which are outstanding in their performance as follows 1. The oxidation of luminol (3-aminophthalhydrazide) (5aimno-2,3-dihydro-l,4 phthalazinedione) 2. lucigenin 3. oxalyl peroxide chloride and its es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In reaction (16), L* is an intermediate product of the photo‐induced luminol and 3 O 2 is triplet oxygen (no 1 O 2 is involved in the reaction). Once the O 2 •− and luminol radicals are generated, they proceed through a series of reactions resulting in the production of blue luminescence (Merényi and others 1986; Popov and Lewin 1994; Schneider 1970). Though all the steps in the detection reaction are not known, an example of possible chemical intermediates in the chemiluminescence of luminol is illustrated in reaction scheme (17) (Pegg and others 2007): …”
Section: Hat Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In reaction (16), L* is an intermediate product of the photo‐induced luminol and 3 O 2 is triplet oxygen (no 1 O 2 is involved in the reaction). Once the O 2 •− and luminol radicals are generated, they proceed through a series of reactions resulting in the production of blue luminescence (Merényi and others 1986; Popov and Lewin 1994; Schneider 1970). Though all the steps in the detection reaction are not known, an example of possible chemical intermediates in the chemiluminescence of luminol is illustrated in reaction scheme (17) (Pegg and others 2007): …”
Section: Hat Assaysmentioning
confidence: 99%
“…In reaction (17), AP * 2− is an excited aminophthalate anion, and AP 2− is the aminophthalate anion at the ground state. The chemical structure of luminol and the aminophthalate anion are discussed by Schneider (1970).…”
Section: Photochemiluminescent (Pcl) Detection Of Water-and Lipidsolumentioning
confidence: 99%
“…The oxidation of 3-aminophthalhydrazide, best known as luminol, is a popular chemiluminescent reaction, and its protagonist role in demonstrations, lectures, and chemistry shows is attested to by the number of articles that have been published since the report of Huntress et al Many improvements have been suggested, ranging from the use of different reactant mixing strategies to the addition of oscillating systems and clock reactions . The emission of light from luminol occurs through an oxidation process requiring air, hydrogen peroxide, or bleach, , typically in the presence of a metal catalyst, such as the iron contained in blood. , The emission of light can also be obtained electrochemically. , The chemiluminescence of luminol displays a bright blue color, which can be modified by the addition of fluorophores . This reaction has widespread practical applications and has been reported as an effective way to introduce forensic and analytical techniques.…”
mentioning
confidence: 99%
“…The assay involves the optical excitation of a photosensitizing substance (Le., luminol) by UV irradiation and its reaction with molecular oxygen followed by luminometric detection. Though the complete reaction mechanism is not known (13,16), the operating principle is believed to be as follows:…”
mentioning
confidence: 99%